Taking Risks in the Target Language: How can we encourage the use of spontaneous speech in the classroom? - Slaughter, Jennifer (2013)
This assignment seeks to explore and reflect on the process of educational action research, and will critically evaluate current theory and practice into the use of the target language in the classroom. I aim to develop effective strategies to encourage the use of spontaneous speech in the classroom and engage with arguments for and against the use of the foreign language by teachers and pupils. I aim to carry out a systematic enquiry into how pupils feel about the use of target language and evaluate what impact it has on their learning. Through the process of action research I aim to explore a variety of strategies that will help teachers understand the role of the target language in the classroom and how to encourage students to express themselves in another language. Theory concerning foreign language teaching and learning will be examined and critiqued against current literature regarding language learning, motivation and the use of spontaneous speech. Throughout my enquiry, I examine strategies proposed through literature based research and student focus groups alike. I will reflect on my findings and evaluate the process throughout this assignment. I explore how modern foreign languages teachers can implement different strategies in their own practice to create a safe teaching and learning environment and encourage the use of spontaneous speech in the classroom.